Two new peltate-leaved species of Begonia L. (Begoniaceae) from northern Vietnam - Radbouchoom, Sirilak; Chen, Wen-Hong; Guo, Shi-Wei; Nguyen, Hieu Quang; Nguyen, Sinh Khang; Nguyen, Hiep Tien; Shui, Yu-Min (Phytotaxa, 2019)
Two new species in Begonia sect. Coelocentrum, Begonia acutis, and B. remusatifolia, have been discovered in the karst regions of northern Vietnam, one of the richest habitats for Begonia. The differences of the two new species were compared with other peltate-leaved species in China and Vietnam, including B. cavaleriei, B. pulvinifera and B. wangii. According to IUCN Red List categories, B. acutis and B. remusatifolia were assigned to the Critically Endangered (CR) and the Endangered (EN) category, respectively.